Do stressful conditions make adaptation difficult? Guppies in the oil-polluted environments of southern Trinidad - Rolshausen, G.; Phillip, D.; Beckles, D.; Akbari, A.; Ghoshal, S.; Hamilton, P.; Tyler, C.; Scarlett, Alan; Ramnarine, I.; Bentzen, P.; Hendry, A. (2015)
© 2015 John Wiley & Sons Ltd. The ability of populations to rapidly adapt to new environments will determine their future in an increasingly human-modified world. Although meta-analyses do frequently uncover signatures of local adaptation, they also reveal many exceptions. We suggest that particular constraints on local adaptation might arise when organisms are exposed to novel stressors, such as anthropogenic pollution. To inform this possibility, we studied the extent to which guppies (Poecilia reticulata) show local adaptation to oil pollution in southern Trinidad. Neutral genetic markers revealed that paired populations in oil-polluted versus not-polluted habitats diverged independently in two different watersheds. Morphometrics revealed some divergence (particularly in head shape) between these environments, some of which was parallel between rivers. Reciprocal transplant experiments in nature, however, found little evidence of local adaptation based on survival and growth. Moreover, subsequent laboratory experiments showed that the two populations from oil-polluted sites showed only weak local adaptation even when compared to guppies from oil-free northern Trinidad. We conclude that guppies show little local adaptation to oil pollution, which might result from the challenges associated with adaptation to particularly stressful environments. It might also reflect genetic drift owing to small population sizes and/or high gene flow between environments.